GIS VECTOR MAP WATERMARKING USING DISCRETE FOURIER TRANSFORM - Ho Choi Hedyatmo, Jun
There are many watermarking methods on GIS Map vector maps that have been developed. One of them is watermarking method using Discrete Fourier Transform or DFT. This watermarking method has many useful properties to make the method robust against several attacks, including rotation, scaling, and translation. But in general, methods that use DFT are not robust against vertex deletion attacks. There are various types of GIS vector map formats, one of which is GeoJSON which is commonly used for web applications. However, this format does not yet have a tool that can help the user to embed and extract watermark directly on geojson.io. In this research, a new method is developed that can increase the robustness of the watermarking method using DFT so that the method is also robust against vertex deletion attacks. After that, the method is also developed in the form of a chrome extension program in the Google Chrome browser which can be used directly on the geojson.io website. The development of a robust method against vertex deletion utilizes a pseudorandom number generator to randomize the index where the watermark is inserted and also marking each indexes actual decimal number by utilizing the 64-bit double precision format in JavaScript, so that the method can be robust against vertex deletion. Then the chrome extension is also developed using the JavaScript language and also uses methods that have been developed previously. Testing of the method is carried out with various attack scenarios and the method is already robust against rotation, scaling, and translation attacks as well as vertex deletion. The Chrome extension is also running well and can run embedding and extracting of the watermark really well.